2019
DOI: 10.1177/2319714519882830
|View full text |Cite|
|
Sign up to set email alerts
|

Examining Maslow’s Hierarchy Need Theory in the Social Media Adoption

Abstract: Social behavior of customers receives a sideline in social media, and the focus appears to be persistent on lead, conversions, and engagement. The psychology of customers is a significant element in the study of social media adoption. Maslow's theory on the hierarchy of needs describes the urge for strong desires after the individual's lower level is satisfied. The study attempts to examine and map the linkages of the Maslow Hierarchy with Social Media Adoption. The study is quantitative and descriptive. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Maslow's hierarchy of needs details basic human needs where physical or extrinsic needs are the foundation or required to be achieved prior and psychological needs are at the top of the pyramid building upon physical needs (Ghatak & Singh, 2019;Maslow, 1943). As Maslow detailed, every person has basic physiological needs.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Maslow's hierarchy of needs details basic human needs where physical or extrinsic needs are the foundation or required to be achieved prior and psychological needs are at the top of the pyramid building upon physical needs (Ghatak & Singh, 2019;Maslow, 1943). As Maslow detailed, every person has basic physiological needs.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Maslow's hierarchy of needs is probably the most wellknown example of a theoretical representation of a social hierarchy. This theory is a mainstay in many fields of psychology education, research and practice, and the content of related studies have provided excellent guidelines on the application of hierarchy theory in social sciences (Ghatak & Singh, 2019). Maslow (1943) described the five categories in his original hierarchy of human needs as follows:…”
Section: Maslow's Hierarchy Of Human Needsmentioning
confidence: 99%
“…With users constantly navigating a vast ocean of information, social media inevitably becomes a go-to source for an attention-deficit world. Moreover, several studies have indicated that social media has been able to build a community which helps people to connect at an emotional level (Ghatak & Singh, 2019). The newfound medium of social connectedness (Waheed et al, 2017) has enabled users to collaborate and create through easy information exchanges.…”
Section: Consumer Motivationsmentioning
confidence: 99%